Acceding countries' gradual integration into the EU single market: Prerequisites, opportunities and hurdles - Peter Becker; Barbara Lippert (Stiftung Wissenschaft und Politik (SWP), 2024)
Since 25 June 2024, the 27 member states of the European Union (EU) have been engaging in accession negotiations with Ukraine and Moldova. The EU wants and needs to provide a strategic response to new geopolitical challenges, especially the Russian war of aggression against Ukraine. At the same time, it intends to accelerate already tough negotiations with the countries of the Western Balkans. Indeed, new proposals are aiming to gradually integrate candidate and acceding countries into specific policy areas of the EU. Accession negotiations regularly focus on these countries' integration into the highly regulated European single market, and thus their adoption of the EU's acquis communautaire with regard to the free movement of people, goods, services and capital. Whether the EU's offer of these country's gradual integration into the EU single market sparks momentum depends on how both sides weigh expected costs and benefits, and whether it is possible to develop concrete measures and timetables for implementation.
Keywords: 320; European Union (EU); accession negotiations; Ukraine; Moldova; Albania; Bosnia and Herzegovina; Kosovo; Montenegro; North Macedonia; Serbia (WB-6); Russian war of aggression against Ukraine; acquis communautaire; free movement of people; goods; services and capital; Moldova; Georgia; cohesion; prosperity